2022
DOI: 10.22323/2.21030203
|View full text |Cite
|
Sign up to set email alerts
|

“Cover your mouth and nose”: communication about health protection behaviors by role models in YouTube COVID-19 videos for children

Abstract: YouTube videos offer a potentially useful vehicle for the communication of science, health, and medical information about COVID-19 to children. Findings from this research showed that primary characters appearing in children's educational YouTube videos about COVID-19 were most often adults, with about an equal number of men and women and few characters from diverse racial and ethnic backgrounds. Primary characters frequently demonstrated and modeled protective health measures. Adult expert characters (medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In particular, parents in their study reported that their children learned a lot of concepts watching cartoons via the platform, for instance, learning some critical ideas about the earthquake. Also, this finding broadly supports the work by Steinke et al [30], as it was reported in their study concerning the use of YouTube videos to help children understand important messages about the fight against transmission of Covid-19. eir study showed that YouTube serves as the source to disseminate information to children about science, health, and medical information during a global pandemic.…”
Section: Youtube Consolidates Teaching and Learningsupporting
confidence: 89%
“…In particular, parents in their study reported that their children learned a lot of concepts watching cartoons via the platform, for instance, learning some critical ideas about the earthquake. Also, this finding broadly supports the work by Steinke et al [30], as it was reported in their study concerning the use of YouTube videos to help children understand important messages about the fight against transmission of Covid-19. eir study showed that YouTube serves as the source to disseminate information to children about science, health, and medical information during a global pandemic.…”
Section: Youtube Consolidates Teaching and Learningsupporting
confidence: 89%
“…A fourth strand discusses the benefits of children’s YouTube engagement. Many have focused on learning, not least during the recent COVID-19 pandemic (Steinke et al, 2022) and the principles by which good educational content can be judged (Neumann & Herodotou, 2020; Shoufan, 2019). Dyosi and Hattingh (2018) considered South African children’s informal learning with YouTube, noting that there was both incidental and self-directed taking place.…”
Section: Introductionmentioning
confidence: 99%
“…Content analytical research on job portrayals in a social media context is even more scarce. The-se existing studies largely focused on counterstreotypical job portrayals (Heizmann & Liu, 2022;Steinke et al, 2024). Therefore, systematic quantitative insights that document how and which types of work values appear most often in TV series and on social media remained overall lacking.…”
mentioning
confidence: 99%